Cultivating a greener plate: understanding consumer choices in the plant-based meat revolution for sustainable diets - Erfanian, Sahar; Qin, Shengze; Waseem, Liaqat Ali; Dayo, Muneer Ahmed (Frontiers in Sustainable Food Systems, 2024)
The implementation of sustainable food systems on a global scale is of utmost importance in order to effectively achieve sustainable diet goals on a world level. Plant-based meat alternatives offer potential replacements for meals derived from animals and serve as a means to transition towards more environmentally sustainable dietary choices. Therefore, in the quest for sustainable diets, comprehending consumer behavior and preferences within the context of the plant-based meat revolution is crucial. The current study is planned to examine the factors that influence the acceptance of plant-based meat alternatives among Chinese people. For this purpose, data collected from 610 individuals through an online survey was analyzed using the partial least square structural equation model. The findings reveal that consumer perceptions, particularly regarding taste, nutrition values, and texture, were found to have a significant impact on the acceptance of plant-based meat alternatives. Effective promotional strategies, availability, and accessibility also play a vital role in influencing consumer preferences for plant-based meat alternatives. The outcomes regarding the significance of health perception and environmental concern in transforming consumer preferences for plant-based meat alternatives are also highlighted. Consumers prioritize plant-based meat alternatives due to their perceived health benefits and favorable environmental impact. Moreover, consumer satisfaction, rooted in meeting or exceeding expectations, signifies the mediating role in the relationship between consumer perceptions and the acceptance of plant-based meat alternatives, which boosts the plantbased meat alternatives' acceptance. Furthermore, the findings underline the mediating role of environmental attitude in the relationship between environmental concerns and plant-based meat alternatives' acceptance, emphasizing the importance of sustainable dietary choices. In general, these findings provide valuable insights into the promotion of sustainable dietary choices, the alignment of consumer behavior with environmentally conscious decisions, and transforming the food systems in light of changing consumer behavior and ecological concerns.